Imbalance in DNA repair machinery is associated with BRAFV600E mutation and tumor aggressiveness in papillary thyroid carcinoma. (5th September 2018) - Lutz, Bruna S.; Leguisamo, Natalia M.; Cabral, Nicole K.; Gloria, Helena C.; Reiter, Keli C.; Agnes, Grasiela; Zanella, Virgilio; Meyer, Erika L.S.; Saffi, Jenifer
Abstract: The involvement of alterations in MLH1, an essential mismatch repair component, in BRAF V600E mutated papillary thyroid carcinoma (PTC) has been suggested to be associated with features of tumor aggressiveness. Thirty-two PTC and surrounding normal thyroid tissues were evaluated for 11 representative DNA repair genes expression. BRAF V600E mutational status assessment and clinicopathological correlations were evaluated for their gene and protein expression. BRAF V600E PTC is associated with lower levels of XPD and MLH1 gene expression. Decrease in MLH1 and XPD mRNA levels in BRAF V600E PTC (but not their protein products) are associated with predictors of poor patient outcomes. Considering the complete subset of patients, MGMT and XRCC2 genes were shown down and upregulated, respectively, in PTC tissues. Low expression of MGMT gene and weak XRCC2 protein expression were correlated with characteristics of tumor aggressiveness. These results suggest that an imbalance in DNA repair gene expression in PTC is associated with aggressive clinicopathological features and BRAF V600E mutation. Highlights: BRAF V600E mutation is the main genetic alteration related to PTC. The role of DNA repair mechanisms in thyroid cancer remains largely unknown. Low mRNA levels of MLH1 and XPD are associated with BRAF V600E mutation and aggressive features of PTC. MGMT and XRCC2 are differentially expressed in PTC. Low expression of MGMT gene and weak XRCC2 protein expression were correlated with tumor aggressiveness. Transcriptional level of DNA repair components may be part of the process in BRAF mutation-promoted PTC tumorigenesis.